(3OdGFd GdfHhIs - (3nCoHh ofnYje CMeO Hf YHO Gddg Hf CMeO GdCUHgGfj,J (B430 (3g` s ((3jMji Hf CHj GdbGSe Hf CHj aQGS Hf HQcGJ Hf SYOGf Hf SdGeI Hf GdRLGL GdMQGfj s)
(3ChdgG (B:s
(3GdMeO ddg Gdehdi GdfYe GdLSGe heSOj GdBdGA GdYXGe GdPj JQGOaJ CjGOjg GdSGHbI s
(3BNQgG (B:s
(3hcGf GHQGgje Udi Gddg Ydjg hSde dCTHg GdfGS Hi NdbkG hoNdbkG BNQ cJGH OdGFd GdfHhI hGdMeO ddg hMSHfG Gddg hfYe Gdhcjd s
(3hGdcJGH HQhGjI SYO GdNjQ Hf eMeO Hf Sgd GdCfUGQj Yf CHj SYO eMeO GHf eMeO GdeWQR Yf GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B282s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B362 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B617 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B177 s
Keywords: (3GdJGQjNs